Methods of tenderization for value-added, hot-boned, restructured, pre-cooked roasts from cows - H.A. Flores; Donald H. Kropf; Melvin C. Hunt; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1986)
Restructured, pre-cooked roasts were prepared from four hot-boned USDA Utility grade cow carcasses. Before forming the roasts, meat was either blade tenderized, manually trimmed of large connective tissue deposits, or both blade tenderized and trimmed. Control roasts received neither treatment. Although trimming minimized the negative effects of connective tissue, blade tenderization was frequently as effective, and sometimes superior, and minimized the high labor costs and shrink losses associated with manual trimming.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Tenderization; Hot-boned; Restructured; Pre-cooked; Roasts